2015
DOI: 10.1063/1.4907284
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of graphene nanowalls on the crystalline silicon for solar cells

Abstract: We developed a simple approach to fabricate graphene/Si heterojunction solar cells via direct growth of graphene nanowalls on Si substrate. This 3D graphene structure was outstanding electrode network and could form fine interface with Si substrate. Moreover, direct growth method not only simplified manufacturing process, but also avoided damages and contaminants from graphene transfer process. The short-circuit current (Jsc) increased greatly and could reach 31 mA/cm2. After HNO3 doping, the energy conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…existence of few layers of graphene sheets with random stacking order in agreement with previous work [24,25]. This observation is also consistent with the high resolution transmission electron microscopy (HRTEM) image of GNWs, as shown in in Figure 3…”
Section: Electrical Characterizationsupporting
confidence: 92%
See 2 more Smart Citations
“…existence of few layers of graphene sheets with random stacking order in agreement with previous work [24,25]. This observation is also consistent with the high resolution transmission electron microscopy (HRTEM) image of GNWs, as shown in in Figure 3…”
Section: Electrical Characterizationsupporting
confidence: 92%
“…Several layers of graphene/graphite sheets with an interplanar spacing of 0.35 nm were observed, confirming the GNWs are made of several layers of graphene [12,[19][20][21]. existence of few layers of graphene sheets with random stacking order in agreement with previous work [24,25]. This observation is also consistent with the high resolution transmission electron microscopy (HRTEM) image of GNWs, as shown in in Figure 3…”
Section: Materials Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…So far, monocrystalline Gr can be directly grown on Ge and Ge/Si substrate . Liu et al successfully grew Gr nanowalls directly on Si substrate with plasma‐enhanced CVD and observed photovoltaic effect . Still, growth of monolayer Gr directly on Si substrate by CVD remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Although high efficiencies have been obtained, it is highly necessary to develop a method of direct growth on Si and apply it to solar cells for practical production. Liu et al reported a direct growth method for a graphene nanowall (GNW) structure on Si for solar cells, and they achieved a PCE of up to 5.1% after chemical doping . Jiao et al used a plasma‐enhanced CVD (PECVD) method to directly grow GNWs on a Si substrate and reported a maximum efficiency of 6.6% with a cell area of 2.5 mm 2 .…”
Section: Direct Growth Of Graphene On the Surface Of Si And Its Applimentioning
confidence: 99%